Congenital nasal cavity stenosis in children with craniosyntosis: A report of 4 rare cases - Liew, Y.T.; Soo, S.S.; Nathan, A.M.; Manuel, A.M. (Elsevier, 2017)
Congenital bony nasal stenosis (CBNS) is a very rare but life-threatening cause of airway obstruction in neonates and infants. This review aims to assess the presentation and early airway management of 4 new cases of craniosynostosis with bilateral nasal cavity stenosis. Patients were treated with endoscopic endonasal widening of the nasal cavity and stenting. All patients were extubated well post-operatively with resolution of symptoms. They remained asymptomatic with stents in situ for at least 6 months with no complications reported. Minimally invasive endoscopic endonasal widening of the nasal cavity with stenting is an effective and safe way of addressing nasal cavity stenosis.